Comparison of Lower Organ Disorders between Wrestlers with Meniscal Injury, Anterior Cruciate Ligament (ACL) and Healthy People in Kermanshah - Tayebeh Mahvar; Somayeh Mahdavikian; Afsaneh Mohammadi; Ferdos Pelarak; Masoud Fallahi; Hamideh Mashalchi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: The present paper studied three lower organ linear disorders, including tibial rotation (rotatingtibia bone around linear axis) (femoral anteversion), femoral normal rotation, and varus complications aspossible risk factors of common sports injuries of knee.Methods: In this comparative descriptive study, 60 men were divided into three meniscal injury, anteriorcross ligament and healthy groups (n=20). All of the participants were current wrestlers at different clubsof Kermanshah province and towns who had at least four years of experience in various sports events.The samples of the injured groups were selected through questionnaire and referral to sports clubs and thehealthy group sample was randomly selected. The healthy individuals had no record of knee injury.Results: The results of the present study revealed that anteversion (internal rotation of femur) affected bothcommon anterior cruciate ligament and meniscal impairments, and tibial rotation only significantly affectedmeniscal injury not anterior cruciate ligament. Also, increase of knee varus angle did not have any effect onmeniscal and anterior cruciate ligament injuries.Conclusion: The results of this study can be helpful to recognize the risk factors of sports injuries.